2018
DOI: 10.1186/s12909-018-1430-9
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of an objective assessment scale for chest tube insertion under ‘direct’ and ‘indirect’ rating

Abstract: BackgroundThere is an increasing need for objective and validated educational concepts. This holds especially true for surgical procedures like chest tube insertion (CTI). Thus, we developed an instrument for objectification of learning successes: the assessment scale based on Objective Structured Assessment of Technical Skill (OSATS) for chest tube insertion, which is evaluated in this study. Primary endpoint was the evaluation of intermethod reliability (IM). Secondary endpoints are ‘indirect’ interrater rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It is essential to promote interprofessional healthcare education and training [43]. Among the 19 studies in the systematic review, 14 only approached chest drain insertion techniques for physicians or medical students [4,[21][22][23][24][25][26][27][28][29][30][31][32][33]. None studied interdisciplinary work in drain insertion or chest drain care, and only 1 presented any protocol for teaching and training students in drainage [28].…”
Section: Interdisciplinary Action and The Quality Of The Proceduresmentioning
confidence: 99%
“…It is essential to promote interprofessional healthcare education and training [43]. Among the 19 studies in the systematic review, 14 only approached chest drain insertion techniques for physicians or medical students [4,[21][22][23][24][25][26][27][28][29][30][31][32][33]. None studied interdisciplinary work in drain insertion or chest drain care, and only 1 presented any protocol for teaching and training students in drainage [28].…”
Section: Interdisciplinary Action and The Quality Of The Proceduresmentioning
confidence: 99%
“…However, a study has reported low correlation coe cients (r < 0.33, p was all > 0.05) between on-site and off-site rating methods when assessing laparoscopy skills among residents [13]. Despite inconsistent ndings in previous research, averaging the off-site ratings of two (or more) evaluators may provide a solution to obtaining reliable results [12]. Apart from intraclass comparison, previous studies have also used validity tests to determine evidence for a strong correlation between total global scores and skill checklist scores from on-site observation in internal medicine education [14] and a moderate correlation for the off-site observation of ultrasound-guided regional anesthesia [15].…”
Section: Introductionmentioning
confidence: 97%
“…Thus, it is crucial to examine whether assessment tools developed for on-site use can be applied off-site to prepare for future practices. Previous studies have utilized off-site assessment of procedural skills among medical students and trainees [10][11][12][13]. An Objective Structured Assessment of Technical Skill (OSATS) was used to evaluate chest tube insertions off-site via video, with an acceptable degree of conformity between an average of two off-site and one on-site evaluation (intraclass correlation coe cient, ICC = 0.76) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [1], the author reported that the given name and family name of all authors were swapped. The details are as follows:…”
mentioning
confidence: 99%